When mistakes affecting one`s own group result in compensation. Evidence of a compensatory own goal effect - Hüffmeier, J.; Stern, J.; Schultze, T. (Psychology of Sport and Exercise, 2020)
Objectives: Although sports team members often value their teams highly, they sometimes make mistakes and thereby unintentionally put their teams at a disadvantage. Thus, they should be motivated to compensate for their mistake to resolve this discrepancy. To test this hypothesis, we studied whether professional soccer players compensate for their own goals by scoring regular goals in the same game (Study 1) and possible processes underlying such compensation efforts (Study 2).